SPIRITUAL WORLDLINESS SEBAGAI ANCAMAN BESAR GEREJA SEPANJANG ZAMAN - Mario Tomi Subardjo (P3TK, Sanata Dharma University, 2015)
Henri de Lubac describes spiritual worldliness as the worst temptation for the Chruch. De Lubacs thought about spiritual worldliness is frequently cited by Pope Francis.This temptation threatens and brings the Church into destruction. The way to prevent this temptation is to understand the churchs identity and mission correctly. If the Church does not maintain the tensions in the way she understands herself, she falls into worldliness. The tendency to understand the Church only in her human or divine dimension will bring the Church into worldliness. This article will help the Church in examining herself, whether she is doing her mission for the greater glory of God or she is doing it for her own glory.